2019
DOI: 10.1016/j.mmcr.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Myrothecium species causing mycotic keratitis: Diagnosis and management

Abstract: We report two cases of keratitis caused by a rare fungus Myrothecium species. Clinical presentation, identification, and management were studied. Both fungi were grown from corneal scraping and identified as M. verrucaria and M. gramineum based on the microbiological techniques and DNA sequencing analysis. Both patients were treated with topical natamycin and or voriconazole/econazole. In the first patient, there was total healing of the with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These patients were treated with topical natamycin and voriconazole. One patient completely recovered, but the other did not, suggesting potential resistance to azoles (7). In our case, A. verrucaria was resistant to fluconazole and echinocandins, and elevated MIC values for itraconazole were observed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These patients were treated with topical natamycin and voriconazole. One patient completely recovered, but the other did not, suggesting potential resistance to azoles (7). In our case, A. verrucaria was resistant to fluconazole and echinocandins, and elevated MIC values for itraconazole were observed.…”
Section: Discussionmentioning
confidence: 57%
“…The importance of A. verrucaria in humans arose from the observation that it produces a potent mycotoxin, which may produce numerous adverse effects, such as the inhibition of protein synthesis, immune suppression, and impairment of alveolar macrophage function (6). Some authors have recently reported Myrotecium spp., also called Albifimbria spp., as the causative agents of keratitis in immunocompetent patients (7). To our knowledge, ours is the only report of A. verrucaria as a causative agent of infection in humans.…”
Section: Introductionmentioning
confidence: 61%
“…For fecal mycobiome (fecal fungi), there was a subtle alteration in sham and CLP mice in all parameters ( Figure 1B ) , partly due to the less abundance of fecal fungi in mice than in humans ( 19 , 42 , 43 ). Although Ascomycota (the phylum of C. albicans , the most prominent fungi in the human gut) was not different between sham and CLP mice, the fecal abundance of Myrothecium , a genus of fungi in the Ascomycota group with a limited report of infection ( 44 ), in CLP mice was less than that in sham mice ( Figure 2B ) . In the fecal virome, the predominant viruses in sham mice were Siphoviridae (double-stranded DNA phages against some Lactobacilli spp.)…”
Section: Resultsmentioning
confidence: 97%
“…They also occur in hay, green feed, and silage from contaminated cereals [19]. What is more, Myrothecium s can contaminate various vegetables e.g., tomato [20]. TCT can also enter human TCT are identified as a significant threat to human and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…They also occur in hay, straw, green feed, and silage from contaminated cereals [19]. What is more, Myrothecium species can contaminate various vegetables e.g., tomato [20]. TCT can also enter human food chains through breakfast cereals, bakery products, snack foods, and beer.…”
Section: Introductionmentioning
confidence: 99%